Key descriptors for fodder trees - Muchugi, Alice; Hanson, Jean; Habte, Ermias; Sime, Yonas; Alemayehu, Arega; Alercia, Adriana Raquel; Cerutti, Ana Laura; López, Francisco (Food and Agriculture Organization of the United Nations, 2023)
The Key descriptors for fodder trees consist of an initial minimum set of characterization and evaluation descriptors for some species of the family Fabaceae (Leguminosae). This strategic set aims at facilitating access to and utilization of these species and it does not exclude the addition of other descriptors later. This work has been done jointly with the International Livestock Research Institute (ILRI) and the FAO International Treaty on Plant Genetic Resources for Food and Agriculture. The list was based on a preliminary set of descriptors developed by ILRI. In addition, internet searches were carried out looking for the most updated information on relevant characteristics and traits. The original list was subsequently integrated with evaluation traits. Special attention was given to the inclusion of descriptors relevant to germplasm utilization and abiotic stresses of particular importance in the context of emerging adverse weather events, which are expected to intensify under current and future climate challenges. The key set of access and utilization descriptors was defined through an online survey, in which 24 experts from 14 different organizations and universities from 13 countries participated. Survey results were subsequently validated in consultation with a Core Advisory Group (see “Contributors”) led by Alice Muchugi and Jean Hanson from ILRI. The strategic set of data standards is designed to facilitate access to and utilization of plant genetic resources for food and agriculture. Together with passport information (Alercia et al. 2015, 2018), descriptors are critical to the effective sharing of characterization and evaluation data and to the efficient use of plant genetic resources for food and agriculture.